Implementation of Strategic Plans on Oil Distributors: A Study on Selected Oil Companies in Kenya - Awale, Yussuf Dahir; Namusonge, Gregory; Warren, Kule Julius (American Journal of Trade and Policy, 2016)
The essence of strategy is to attempt to relate the organization to the changes in the environment. For any organization, strategy helps in interrogating the long term plans and ensuring that there is harmony between the vision, mission, objectives, core values, activities and its environment. Strategy formulation and implementation are core management functions. The developed strategy may be good but if its implementation is poor the intended strategic objectives may not be achieved. To ensure survival and success, firms do not only need to formulate strategies that seek to constantly maintain a match between the organization and its environment but also must ensure appropriate execution of strategy at all levels. Success therefore calls for proactive approach to business. The study aimed at identifying the determinants of strategy implementation plans on oil distributors in Kenya. Specifically, the study attempted to achieve the following objectives: to determine the effect of organizational structure; organizational culture; leadership; resource allocation and to establish the effect of communication on implementation of strategic plans on oil distributors in Kenya. The study was based on resource-based theory; dynamic capability theory and knowledge-based view theory. The study adopted a survey design that had used cross-sectional survey approach to collect data. The population of the study comprised of 14 oil distributors in Kenya based in Nairobi County. The target respondents comprised of 64 business owners and 136 managers therefore comprising of a target population of 200 respondents. A sample size of 60 respondents was selected for the study. Primary data was collected through semi-structured questionnaires. Data was coded in SPSS and Excel software for analysis where the tables of frequencies, percentage, mean and standard deviation was extracted for presentation of data. Inferential statistics was done to establish the relationship between the implementation of strategic plans and the five independent variables. The outcome of the study was to establish whether organizational structure; organizational culture; leadership; resource allocation and corporate communication affect the implementation of strategic plans in the oil distributors sector in Nairobi County. The research recommends that for oil distributors to improve on the implementation of strategic plans they need to enhance of teamwork, accountability, transparency and communication.